Replacement of alpha-galactosidase A in Fabry disease: effect on fibroblast cultures compared with biopsied tissues of treated patients - Keslová-Veselíková, Jana; Hůlková, Helena; Dobrovolný, Robert; Asfaw, Befekadu; Poupetová, Helena; Berná, Linda; Sikora, Jakub; Golán, Lubor; Ledvinová, Jana; Elleder, Milan (Virchows Archiv, 2008)
The function and intracellular delivery of enzyme therapeutics for Fabry disease were studied in cultured fibroblasts and in the biopsied tissues of two male patients to show diversity of affected cells in response to treatment. In the mutant fibroblasts cultures, the final cellular level of endocytosed recombinant alpha-galactosidases A (agalsidases, Fabrazyme, and Replagal) exceeded, by several fold, the amount in control fibroblasts and led to efficient direct intra-lysosomal hydrolysis of ((3)H)Gb3Cer. In contrast, in the samples from the heart and some other tissues biopsied after several months of enzyme replacement therapy (ERT) with Fabrazyme, only the endothelial cells were free of storage. Persistent Gb3Cer storage was found in cardiocytes (accompanied by increase of lipopigment), smooth muscle cells, fibroblasts, sweat glands, and skeletal muscle. Immunohistochemistry of cardiocytes demonstrated, for the first time, the presence of a considerable amount of the active enzyme in intimate contact with the storage compartment. Factors responsible for the limited ERT effectiveness are discussed, namely post-mitotic status of storage cells preventing their replacement by enzyme supplied precursors, modification of the lysosomal system by longstanding storage, and possible relative lack of Sap B. These observations support the strategy of early treatment for prevention of lysosomal storage.
Keywords: Male; lidé středního věku; konfokální mikroskopie; alfa-galaktosidasa; fibroblasty; kultivované buňky; Myocardium; Humans; Microscopy, Confocal; Middle Aged; alpha-Galactosidase; mužské pohlaví; Genetic Therapy; myokard; Cells, Cultured; genetická terapie; Fabry Disease; Fabryho nemoc; Biopsy; lidé; Fibroblasts; biopsie